Formation of CaCO3 deposits on OMS‐2 surface to synergistically promote peroxymonosulfate activation and organic dyes degradation. (4th April 2019) - Zou, Qiancheng; Wei, Yi; Wang, Shuai; Xie, Jinyan; Xu, Aihua; Li, Xiaoxia
Abstract : The development of green and efficient catalysts for peroxymonosulfate (PMS) activation and organic pollutants degradation has received widespread attention. In this study, the hybrid CaCO3 /OMS‐2 catalysts were prepared by a simple precipitation approach and characterized by X‐ray powder diffraction, N2 adsorption–desorption, scanning electron microscopy, transmission electron microscopy, X‐ray photoelectron spectroscopy and cyclic voltammetry. It was found that deposition of CaCO3 on OMS‐2 surface can weaken the Mn‐O bond by formation of Ca‐O‐Mn bond. The interactions between CaCO3 and OMS‐2 significantly enhanced Acid Orange 7 degradation in the presence of PMS with a pseudo‐first‐order kinetic constant of 0.21 min −1, which was much higher than those of OMS‐2 (0.026 min −1 ) and CaCO3 (0.021 min −1 ). The CaCO3 /OMS catalysts were also much more efficient than other reported OMS‐2 hybrid catalysts, and could be performed over a wide solution pH and for other organic dyes degradation. Sulfate and hydroxyl radicals were formed from the oxidation of low valent manganese species by PMS as the active species in the system. This study can provide a simple method for the design of efficient manganese‐based hybrids for wastewater remediation via PMS activation. Abstract : The interactions between CaCO3 and OMS‐2 significantly enhance Acid Orange 7 degradation in the presence of peroxymonosulfate.